Artificial Intelligence-Based Mathematics Learning Media Integrated With Islamic Values: What’re The Experts Think About? - Kharisma, Nafilah Ulfah; Nursupiamin, Nursupiamin; Elfira, Riska (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study aims to develop an Islamic-integrated mathematics learning media based on Artificial Intelligence (AI), with the expectation of enhancing learning effectiveness in the digital era. The research employed the ADDIE development model, which consists of the stages of analysis, design, and development. The participants in this study were three experts who validated the developed media, named